2014
DOI: 10.1016/j.molcel.2014.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Modification of PCNA by ISG15 Plays a Crucial Role in Termination of Error-Prone Translesion DNA Synthesis

Abstract: In response to DNA damage, PCNA is mono-ubiquitinated and triggers translesion DNA synthesis (TLS) by recruiting polymerase-η. However, it remained unknown how error-prone TLS is turned off after DNA lesion bypass to prevent mutagenesis. Here we showed that ISG15 modification (ISGylation) of PCNA plays a key role in TLS termination. Upon UV irradiation, EFP, an ISG15 E3 ligase, bound to mono-ubiquitinated PCNA and promoted its ISGylation. ISGylated PCNA then tethered USP10 for deubiquitination and in turn the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
128
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 38 publications
1
128
0
Order By: Relevance
“…We first confirmed that the two mutants lost the E3 ligase activity. Multiple cellular proteins have been reported as the substrates of TRIM25, such as RIG-I, 14-3-3␦, AMF, ATBF1, and PCNA (28,30,(35)(36)(37). We reasoned that TRIM25 overexpression would increase the ubiquitination levels of these proteins as well as that of some unidentified cellular proteins.…”
Section: Resultsmentioning
confidence: 98%
“…We first confirmed that the two mutants lost the E3 ligase activity. Multiple cellular proteins have been reported as the substrates of TRIM25, such as RIG-I, 14-3-3␦, AMF, ATBF1, and PCNA (28,30,(35)(36)(37). We reasoned that TRIM25 overexpression would increase the ubiquitination levels of these proteins as well as that of some unidentified cellular proteins.…”
Section: Resultsmentioning
confidence: 98%
“…While it is accepted that the consequences of the inactivation of a single Y-pol must be different from those arising from the global block of all Y-pols, with the exception of p21 [45], the analysis of most inhibitors has been restricted to Polη [36, 51, 5357, 60, 61]. Moreover, the overexpression/stabilization of TLS inhibitors should be exploited to support their negative role in TLS.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Certain accessory proteins are also critical for TLS. 3236 However, many questions, including how these TLS pols are selected and recruited for a particular lesion and how the switch among different pols is coordinated, remain unanswered at present. In mammalian cells, TLS is conducted by pol η, pol κ, pol ι, and Rev1 of the Y-family pols and pol ζ of the B-family enzymes.…”
mentioning
confidence: 99%